2013
DOI: 10.1155/2013/283985
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Activated Platelet-Derived Growth FactorβReceptor and Ras-MAP Kinase Pathway in Equine Sarcoid Fibroblasts

Abstract: Equine sarcoids are skin tumours of fibroblastic origin affecting equids worldwide. Bovine papillomavirus type-1 (BPV-1) and, less commonly, type-2 are recognized as etiological factors of sarcoids. The transforming activity of BPV is related to the functions of its major oncoprotein E5 which binds to the platelet-derived growth factor β receptor (PDGFβR) causing its phosphorylation and activation. In this study, we demonstrate, by coimmunoprecipitation and immunoblotting, that in equine sarcoid derived cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 60 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Cells grown for 2 days on coverslips were washed, fixed, permeabilized and subjected to background blocking as previously reported 17 . Anti-HA, anti-p53 and anti-E6AP antibodies were applied for 2 h at room temperature (rt) in a humidified chamber at 1:50 dilution in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Cells grown for 2 days on coverslips were washed, fixed, permeabilized and subjected to background blocking as previously reported 17 . Anti-HA, anti-p53 and anti-E6AP antibodies were applied for 2 h at room temperature (rt) in a humidified chamber at 1:50 dilution in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Cell pellets were subjected to total protein extraction, protein quantification, sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) and Western blotting (WB) as described previously (30). Membranes were incubated with the following primary antibodies overnight (O/N) at 4 • C at 1:1,000 dilution: anti-TERT (rabbit polyclonal, Rockland #600-401-252), anti-cMyc (mouse monoclonal, Santa Cruz Biotechnology, #sc-40, clone 9E10), anti-MMP-1 (mouse monoclonal, Santa Cruz Biotechnology, #sc-21731, clone 3B6) and anti-MMP-2 (rabbit polyclonal, Neomarkers, #RB-1537-P0), anti-MMP-9 (mouse monoclonal, Millipore, #MAB3309, clone 56-2a4), and β-actin (mouse monoclonal, Calbiochem #CP01-1EA, clone JLA20) or tubulin (mouse monoclonal, Santa Cruz Biotechnology, #sc-23948, clone B-5-1-2).…”
Section: Western Blottingmentioning
confidence: 99%
“…Cells grown for 48 h on coverslips were washed, fixed, permeabilized, and subjected to background blocking as previously reported (30). Primary antibodies anti-TERT, anti-MMP-2, and anti-MMP-9 at 1:50 dilution in PBS were applied for 2 h at rt in a humid chamber.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Tendons are responsible for transferring the forces exerted by muscles to the bone tissue, thus enabling locomotion. It has been shown that tendons change their metabolism in response to mechanical forces and that, depending on the intensity of the mechanical stimulus, tendon fibroblasts secrete various proteins, such as collagen I and cyclooxygenase [ 1 5 ]. Although tendons are regarded as low metabolism tissue, under conditions of stress and during healing they can alter their metabolism significantly, leading to the secretion of various growth factors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%